AB1250 Measurement of joint temperature by microwave radiometry as a novel and simple method for the detection of synovial inflammation: A pilot study. (23rd January 2014) - Zampeli, E.; Raftakis, I.; Michelongona, A.; Nikolaou, C.; Elezoglou, A.; Antoniadis, C.; Toutouzas, K.; Sfikakis, P.P.
Abstract : Background: Microwave Radiometry (MR) is a non-invasive method which rapidly (30 sec) measures the temperature of internal tissues in vivo . MR functions by determining the natural electromagnetic radiation from internal tissues at microwave frequencies, based on the principle that radiation's intensity is proportional to the temperature of the tissue. Using the currently available device (RTM 01 RES, Bolton, UK) tissue temperature can be measured at a depth of 3-7cm with an accuracy of ±0.2°C. Objectives: To examine the hypothesis that MR may detect increased local temperature associated with synovial inflammation, which can be otherwise diagnosed by ultrasound. Methods: The knees of consecutive non-febrile healthy controls and patients with rheumatoid arthritis or osteoarthritis were examined by MR by placing the sensor on naked skin at the upper one third of the thigh (used as control point) and on the upper pole of the patella to assess the joint's temperature. Joint ultrasound (linear array probe, 5-12MHz) was performed immediately after by an experienced ultrasonographer who was blinded to the subject's history and temperature readings. The presence of fluid and synovitis was recorded using gray scale and power Doppler respectively; possible correlations between ultrasound and MR findings were explored. Results: Knee and thigh temperatures in healthy subjects were 32.3±1.1°C and 34.1±0.9 (mean±SD) respectively, with a difference of -1.76±0.2°C (n=10). Of the knees from 13 arthritis patients examined, 11 had increased fluid amount in the suprapatellar bursa (>2.4mm midline sagittal) and 15 had normal findings. Knee temperature in these two subgroups was 32.6±1.2 vs 31.8±1.2°C (p=0.096), whereas thigh temperature was 33.1±0.6 vs 33.5±0.3°C, respectively (p=0.063). However, in knees with fluid the temperature difference (ΔT°) between patella and the control point was lower by 3-fold than in those without (-0.6±1.0 vs -1.8±1.1°C, p=0.01). Synovitis was evident in 3 of 26 patients' knees with power Doppler findings indicative of grade 2 inflammation. Knee temperature was higher in joints with synovitis (33.9±0.4 vs 31.9±1.1°C, p=0.005), whereas ΔT° between patella and the control point was also significantly lower in the presence of synovitis (-0.6±0.6 vs -1.5±1.1°C, p=0.005). Conclusions: Increased knee joint temperature can be readily detected by MR, a safe, non-invasive, easy-to-perform, objective and rapid method, and reflect synovial inflammation as evidenced by ultrasonography. Since thermal changes cannot be sensed by skin palpation in every joint, whereas they may precede inflammatory changes that can be detected by imaging methods, it is a challenge to refine MR methods and produce sensors for smaller joints that could detect increased temperature in precise and/or targeted depths (i.e. specifically at synovium). Studies to reveal whether or not MR can serve as an objective tool to detect early synovitis in the clinical setting are warranted. Disclosure of Interest: None Declared